Use of Artificial Intelligence (AI) as A Support for Technology-Based Learning in Developing Teacher Creativity and Innovation - Nuhzatul Ainiyah; Ni’matus Shofiah; Ayu Wulandari (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2024)
Digitalization in education encourages teachers to adapt in creating learning experiences that are relevant and meet the needs of students in the technological era. Artificial Intelligence (AI) technology plays a crucial role in enhancing the quality of education. AI supports teachers by providing tools that promote creativity and innovation in teaching. This study uses a qualitative literature review approach to analyze the development of AI technology in supporting learning, identify types of AI that can enhance teachers' creativity and innovation, and explore the challenges and opportunities of using AI in education. The findings of the study indicate thatAI plays a crucial role in supporting teachers' creativity and innovation. It helps enhance the quality of learning through tools that enable personalization and efficiency in the teaching process. Although AI holds great potential, its implementation in education still faces challenges, such as limited training for teachers and the risk of over-dependence on technology